Mesenchymal Stem Cell Fate: Applying Biomaterials for Control of Stem Cell Behavior - Anderson, Hilary J.; Sahoo, Jugal Kishore; Ulijn, Rein V.; Dalby, Matthew J. (Frontiers in Bioengineering and Biotechnology, 2016)
The materials pipeline for biomaterials and tissue engineering applications is under continuous development. Specifically, there is great interest in the use of designed materials in the stem cell arena as materials can be used to manipulate the cells providing control of behavior. This is important as the ability to “engineer” complexity and subsequent in vitro growth of tissues and organs is a key objective for tissue engineers. This review will describe the nature of the materials strategies, both static and dynamic, and their influence specifically on mesenchymal stem cell fate.